PROBLEMATIKA PENERAPAN PRINSIP NON REFOULEMENT DALAM PENANGANAN PENGUNGSI DI INDONESIA - Korpus Kristi Yohanes Darmo (Universitas Borneo Tarakan, 2021)
Indonesia, a country that does not ratify the 1951 Convention and the 1967 Protocol, is indirectly bound by the principle of non-refoulement. The attachment occurs since Indonesia has approved various provisions in international law comprising the principle of non-refoulement. Moreover, the principle is acknowledged as a juz cogen in international law, although in its application, there are both binding and causal clauses that can be excluded by the state. The enforcement of the non-refoulement principle ultimately poses some problems for Indonesia in handling foreign refugees. The first problem is that the existence of refugees is against Indonesian immigration law which upholds a selective policy. Secondly, a status determination, fully mandated by the United Nations High Commissioner for Refugees (UNHCR), does not have clear standards which in turn creates new problems. Then, the vague implementation of resettlement also becomes an issue for Indonesia, in which not all refugees can get resettlement. The 1951 Convention and 1967 Protocol mandate UNHCR to carry out voluntary repatriation, local integration and resettlement as a permanent solution for refugees; however, refugees in Indonesia cannot implement the local integration. Presidential Regulation Number 125 of 2016, a legal protection for handling foreign refugees in Indonesia, cannot be categorized as positive law based on the lex specialis principle of Law Number 6 of 2011 on Immigration. Hence, Indonesia must immediately revise Presidential Regulation Number 125 of 2016 on Handling Foreign Refugees, make efforts to review the status of refugees rejected in the resettlement process and draw up regulations for handling refugees in the form of a law.